A magyar regionális fejlődés sajátosságai a határkutatások szemszögéből = Characteristic features of Hungarian regional development from the aspects borders researches - Baranyi, Béla (Közép-Európai Közlemények, 2017)
The presentation is a summary of the experiences of régiónál development over a quarter of a century, from the aspect of Hungárián bordér researches. European integration and the unfurling Schengen process changed the relationship of Hungárián régiónál Science and bordér researches in the interpretation of territorial processes. There was a gradual shift of focus by régiónál policies: the so-called “Trianon-syndrome”, the analysis of the traditional controlling and restricting functions of State borders was gradually replaced by the analysis of the character of cross-border cooperations. From the point of view of development policy, the tight relationship of régiónál Science and bordér research was founded by the need fór the utilisation of internál and extemal resources, which is the prime motivation of cross-border relations. It is beyond doubt that the use of Hungárián and even more so the EU régiónál supports can effectively serve the moderation of the development disparities of bordér regions, the catching up of the extemal (bordér) peripheries, the “unification” of the spatial structural functions disintegrated by the Peace Treaty of Trianon, the creation and cohesion of a functioning macro-regional economic space in the Carpathian Basin - and all in all the issue of European integration, the improvement of neighbourhood relations.